ChemInform Abstract: Hetereogeneous CuII‐Catalyzed Solvent‐Controlled Selective N‐Arylation of Cyclic Amides and Amines with Bromo‐iodoarenes. Issue 18 (17th April 2014) - Kundu, Debasish; Bhadra, Sukalyan; Mukherjee, Nirmalya; Sreedhar, Bojja; Ranu, Brindaban C.
Abstract An efficient protocol for the N‐arylation of different cyclic amides and amines under convenient conditions is described.